Clinical, radiological, therapeutic and prognostic differences between MOG-seropositive and MOG-seronegative pediatric acute disseminated encephalomyelitis patients: a retrospective cohort study - Dong, Xueshan; Jiang, Yan; Yuan, Ping; Fan, Xiao; Ma, Jiannan; Wu, Peng; Jiang, Li; Li, Xiujuan (Frontiers in Neuroscience, 2023)
Objective: To compare clinical, radiological, therapeutic and prognostic differences between acute disseminated encephalomyelitis (ADEM) in children with positive and negative myelin oligodendrocyte glycoprotein (MOG) antibodies. Methods: We retrospectively collected all available data of children diagnosed with ADEM testing serum MOG antibodies in Children's Hospital of Chongqing Medical University from January 2017 to May 2021. Results: A total of 62 patients were included in our cohort, of which 35 were MOG-seropositive and 27 were MOG-seronegative. ADEM without MOG antibodies presented significantly more seizures (P=0.038) and cranial nerve (III-XII) palsy (P=0.003). Isolated serum leukocytosis was more common in ADEM children with MOG antibodies (P<0.001). In MOG-seronegative group, the duration of the first-course oral prednisolone tapering after acute treatments was significantly longer (P=0.028). Relapses only appeared in MOG-seropositive children (P=0.017). Scored by two neurological function scores, it showed that MOG-seropositive children had milder neurological disability status at onset (P=0.017 and 0.025 respectively) but there was no difference during follow-up. Conclusion: In summary, differences between MOG-seropositive and MOG-seronegative ADEM children in clinical manifestations and auxiliary examinations lacked significance and specificity, so the early identification was difficult. MOG- seropositive children were more likely to relapse and had a slower steroid tapering. Besides, MOG-seronegative children tended to have more severe neurological impairments at onset with no difference during follow-up.